Adolescents’ internalizing and externalizing symptom trajectories in relation to early-life parental depressive symptoms - Csajbók, Zsófia; Brennan Kearns, Pavla (European psychiatry, 2025)
While risk factors for children's internalizing and externalizing symptom trajectories have been widely studied, their association with parental depressive symptom trajectories has yet to be explored. We used data from a prospective birth cohort of 2,542 Czech children and their parents. Children reported internalizing and externalizing symptoms at ages 11, 15, and 18 years. Parental depressive symptoms were assessed eight times from the prenatal period to the child's age of 11 years. Latent Class Growth Mixture Modeling identified parallel trajectories of children's symptoms. Five parental depressive symptom trajectories were adopted from previous research. We identified four distinct classes of children's symptom trajectories: (1) low internalizing and low externalizing (64%), (2) low internalizing and high externalizing (8%), (3) elevated internalizing and elevated externalizing (19%), and (4) high internalizing and elevated externalizing symptoms (9%). Children were more likely to experience any symptoms if their mothers had elevated depressive symptoms. High maternal and paternal depressive symptoms were associated with high internalizing and elevated externalizing symptoms in children. Constantly depressed mothers with elevated depressive symptoms in fathers had a high likelihood of any symptom trajectories in children. Other strong predictors of children's symptom trajectories included parental relationship status (e.g., divorce), prior abortion, as well as children's sex, urban versus rural residence, stressful life events, and self-esteem. Parents' and children's mental health trajectories are interconnected. Given the strong influence of parental relationship dynamics on both parental and child mental health, interventions should prioritize mitigating relationship strains to support family well-being.